2020
DOI: 10.2147/copd.s211838
|View full text |Cite
|
Sign up to set email alerts
|

<p>Demographic, Clinical and Management Characteristics of Newly Diagnosed COPD Patients in Turkey: A Real-Life Study</p>

Abstract: In order to determine the clinical and sociodemographic characteristics of newly diagnosed treatment-naïve asthma and COPD patients in Turkey, a multicenter study in 2012 was initiated. We aimed to investigate the characteristics and therapies of COPD patients in the original study in more detail. Patients and Methods: This nationwide , multicentric, non-interventional, prospective, reallife observational cohort study was conducted in 122 centers. The newly diagnosed patients were not receiving any treatment b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…It was demonstrated that more than 70% of the patients were overtreated. The most commonly prescribed medication was LABA+LAMA+ICS with a rate of 54.9% (10). In another multi-center cross-sectional study from Turkey called ALPHABET, 1610 patients with COPD were recruited and it was reported that 41.1% of the patients with COPD were in group A according to the GOLD 2013.…”
Section: Pharmacologic Treatment In Turkeymentioning
confidence: 99%
See 1 more Smart Citation
“…It was demonstrated that more than 70% of the patients were overtreated. The most commonly prescribed medication was LABA+LAMA+ICS with a rate of 54.9% (10). In another multi-center cross-sectional study from Turkey called ALPHABET, 1610 patients with COPD were recruited and it was reported that 41.1% of the patients with COPD were in group A according to the GOLD 2013.…”
Section: Pharmacologic Treatment In Turkeymentioning
confidence: 99%
“…The narrative review of chronic obstructive pulmonary disease management in Turkey: medical treatment, pulmonary rehabilitation and endobronchial volume reduction national studies (8,9). In a recent multicenter study from Turkey, it was found that 56.3% of 776 patients with newly diagnosed COPD were current smokers, 38.1% of whom were ex-smokers and 7.2% had history of biomass exposure (10). Biomass such as organic fuels usually cause indoor air pollution in rural areas of Turkey.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 However, early diagnosis and good treatment improve the quality of life and the average life expectancy of such patients. 4 The majority of COPD cases experience frequent exacerbations which deteriorate their health and lung reserves. Therefore, it is highly recommended to standardize COPD and its exacerbation treatment protocols according to the Conflict of interest: The authors declared no conflict of interest exists.…”
Section: Introductionmentioning
confidence: 99%
“…DOI: https://doi.org/10.37018/VBDJ8042 national or international guidelines. 4 Out of all the current COPD treatment guidelines, Global Initiative for obstructive Lung Disease (GOLD) recommendations are the most widely used by clinicians. 5 This strategy paper is helpful not only in the management of stable COPD but also for its exacerbations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation